State of the Art in the Studies on Crotamine, a Cell Penetrating Peptide from South American Rattlesnake. (15th January 2014) - Kerkis, Irina; Hayashi, Mirian A. F.; Prieto da Silva, Alvaro R. B.; Pereira, Alexandre; De Sá Júnior, Paulo Luiz; Zaharenko, Andre J.; Rádis-Baptista, Gandhi; Kerkis, Alexandre; Yamane, Tetsuo
Abstract : Animal venoms comprise a naturally selected cocktail of bioactive peptides/proteins and other molecules, each of which playing a defined role thanks to the highly specific interactions with diverse molecular targets found in the prey. Research focused on isolation, structural, and functional characterizations of novel natural biologics (bioactive peptides/proteins from natural sources) has a long way to go through from the basic science to clinical applications. Herein, we overview the structural and functional characteristics of the myoneurotoxin crotamine, firstly isolated from the South American rattlesnake venom. Crotamine is the first venom peptide classified as a natural cell penetrating and antimicrobial peptide (CPP and AMP) with a more pronounced antifungal activity. In contrast to other known natural CPPs and AMPs, crotamine demonstrates a wide spectrum of biological activities with potential biotechnological and therapeutic values. More recent studies have demonstrated the selective in vitro anticancer activity of crotamine. In vivo, using a murine melanoma model, it was shown that crotamine delays tumor implantation, inhibits tumor cells proliferation, and also increases the survival of mice engrafted with subcutaneous melanoma. The structural and functional properties and also the possible biotechnological applications of minimized molecules derived from crotamine are also discussed.